Penggunaan Alat Komunikasi Melalui Aplikasi Whatsapp Pada Pembelajaran Seni Tari Kelas XI IPS 3 Di SMA Negeri 5 Padang - Hafiidha Gusti Haryani; Yuliasma Yuliasma (SENDRATASIK UNP, 2020)
This study aims to determine and describe the impacts of using WhatsAppas a communication tool in dancelearningfor class XI IPS 3 at SMA Negeri 5 Padang. This is a qualitative research using a descriptive method. The main instrument in this studywas the researcher itself and was assisted by supporting instruments such as cameras, photos, and interviews conducted online through WhatsApp. The data were collected through observation, interview, and documentation. The data used were primary and secondary data. The data analysis was conducted by clarifying each theme, adjusting and comparing the data, and describing the data. The results show that the use of communication tools through WhatsApp in dance learning for class XI IPS 3 at SMA N 5 Padang has both negative and positive impacts on teacher and students. The positive impacts for teacher are that it is easier for teacher to share information to students, andthe teacheris responsible for assignments. The teacher acts as a motivator.The negative impacts for teacherare that the materialshave not been presented completely, it is difficult for teacher to monitor student activities, facilities are limited, the teacher’shealth is bothered, and the learning process becomes less effective and efficient. The positive impacts for students are they areresponsiblefor the assignments given by the teacher, they are discipline with attendance, and they have enthusiasm in learning. The negative impacts for students are difficulty in understanding the material, increasing parental expenses (internet data), difficulty in focusing on learning, time problem, learning concentration problem, and health threat.